Cardiac Arrhythmias Requiring Electric Countershock during the Neonatal Period-A Systematic Review - Nathalie Oeffl; Marlies Krainer; Stefan Kurath-Koller; Martin Koestenberger; Bernhard Schwaberger; Berndt Urlesberger; Lukas P. Mileder (MDPI AG, 2023)
Background: In neonates, cardiac arrhythmias are rare. Electric countershock therapy is an effective alternative to drug therapy for neonatal arrhythmias. There are no randomized controlled studies investigating electric countershock therapy in neonates. Objective: To identify all studies and publications describing electric countershock therapy (including defibrillation, cardioversion, and pacing) in newborn infants within 28 days after birth, and to provide a comprehensive review of this treatment modality and associated outcomes. Methods: For this systematic review we searched MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), and Cumulative Index to Nursing and Allied Health Literature (CINAHL). All articles reporting electric countershock therapy in newborn infants within 28 days after birth were included. Results: In terms of figures, 113 neonates who received electric countershock due to arrhythmias were reported. Atrial flutter (76.1%) was the most common arrhythmia, followed by supraventricular tachycardia (13.3%). Others were ventricular tachycardia (9.7%) and torsade de pointes (0.9%). The main type of electric countershock therapy was synchronized cardioversion (79.6%). Transesophageal pacing was used in twenty neonates (17.7%), and defibrillation was used in five neonates (4.4%). Conclusion: Electric countershock therapy is an effective treatment option in the neonatal period. In atrial flutter especially, excellent outcomes are reported with direct synchronized electric cardioversion.